2019
DOI: 10.1111/imcb.12246
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory effects of measles‐mumps‐rubella vaccination on persistence of heterologous vaccine responses

Abstract: It is proposed that measles‐containing vaccines have immunomodulatory effects which include a reduction in all‐cause childhood mortality. The antibody response to heterologous vaccines provides a means to explore these immunomodulatory effects. This is the first study to investigate the influence of measles‐mumps‐rubella (MMR) vaccine on the persistence of antibodies to a broad range of heterologous infant vaccinations given in the first year of life. In total, 319 children were included in the study. All infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…For example, the Bacille Calmette-Guérin (BCG) vaccine for Mycobacterium tuberculosis, used in countries where tuberculosis is still prevalent, modulates the innate immune response and induces protection against non-mycobacterial species and some types of cancers [16][17][18][19] . Similar effects have been observed with the measles, mumps, and rubella (MMR) vaccine 20,21 .…”
Section: Introductionsupporting
confidence: 60%
“…For example, the Bacille Calmette-Guérin (BCG) vaccine for Mycobacterium tuberculosis, used in countries where tuberculosis is still prevalent, modulates the innate immune response and induces protection against non-mycobacterial species and some types of cancers [16][17][18][19] . Similar effects have been observed with the measles, mumps, and rubella (MMR) vaccine 20,21 .…”
Section: Introductionsupporting
confidence: 60%
“…Interestingly, we found negative correlations between responses to the live-vaccines measles, mumps and rubella, and non-live vaccines (MenC, tetanus, Hib). The finding is not easily explained as several studies have shown that simultaneous or delayed administration of MMR does not influence antibody concentrations to non-live vaccines ( 11 14 ).…”
Section: Discussionmentioning
confidence: 87%
“…Live attenuated vaccines, including BCG (Bacillus Calmette Guerin) and MMR (measles, mumps and rubella) are known to activate innate immune responses in addition to vaccine-specific immune responses, leading to a bystander or off-target effects on the immune system (10)(11)(12)(13)(14). The role of COVID vaccines in inducing such an effect remains unexplored.…”
Section: Discussionmentioning
confidence: 99%